Effect of feed and health packages on the performance of village small ruminants in northern Ghana - Avornyo, Franklin K.; Ayantunde, Augustine A.; Shaibu, M.T.; Konlan, Solomon Pigangsoa; Karbo, N. (ScopeMed, 2015)
The objective of this study was to assess the productivity of small ruminant through the introduction of improved health care and feeding strategies into small ruminant production systems. The General Linear Model of SAS was used to compare means after fitting sources of variation to models. Growth rate of treatment animals was higher than that of control animals (P<0.05). Lambs grew about twice as fast as kids (P<0.05). Lower mortality rate was observed in treatment animals compared to control (P<0.05), partly contributing to higher birth rate observed in treatment animals (P<0.0001). A strong interaction was observed between community and type of animal (P<0.001). A net gain of US$5.65 was observed for each treatment animal compared to US $8.58/control animal (P<0.05). However, these profit margins were significantly affected (P<0.05) by the management practices of the farmers. The package resulted in increased birth rates so the concentrate feed could be tried on pregnant and lactating females.